2003
DOI: 10.1586/14737167.3.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of emergency contraceptive pills in the public sector in the USA

Abstract: Emergency contraception, which prevents pregnancy after unprotected sexual intercourse, has the potential to significantly reduce the incidence of unintended pregnancy and the consequent need for abortion. The cost-effectiveness of emergency contraceptive pills in the public sector in the USA is determined. The cost-savings when a single emergency contraceptive treatment is provided following unprotected intercourse are modeled along with when women are provided emergency contraceptive pills in advance. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Emergency contraception reduces expenditures on medical care by preventing unintended pregnancies, which are expensive. Emergency contraceptive pills have been shown to be cost saving in the United States and in Canada 20–23 . Here we show that they are also cost‐saving in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency contraception reduces expenditures on medical care by preventing unintended pregnancies, which are expensive. Emergency contraceptive pills have been shown to be cost saving in the United States and in Canada 20–23 . Here we show that they are also cost‐saving in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has challenged earlier analyses of the public health impact of emergency contraception. Whereas many studies pointed to the drug's potential to reduce rates of unintended pregnancy and the cost savings of preventing pregnancies (Trussell et al 1995(Trussell et al , 1997a(Trussell et al , and 1997bTrussell and Shochet 2003), these claims have been contested by recent studies that have shown no association between expanded access to emergency contraception and reduced rates of unintended pregnancy and induced abortion (see reviews by Raymond et al 2007 andPolis et al 2007). Some of these recent studies are now being cited by antichoice groups to argue against expanding access to emergency contraceptive pills.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the cost effectiveness of EC in the general population may be overestimated as well. [16][17][18][19][20] Alternatively, non-enrolled women may be at higher risk of pregnancy than women in EC clinical trials because they are ineligible to enrol due to additional acts of UPSI in a cycle or because they decline to enrol, preferring a 'proven' EC regimen over an experimental regimen. In all randomised EC trials, as in our trial, enrolment is restricted to women who have only had one act of UPSI 72 (or 120) hours before they present at the clinic.…”
Section: Discussionmentioning
confidence: 99%